Bi-axial flexural strength of dual-polymerizing agents cemented to human dentin after photo-activation with different light-curing systems - Nadia Malek A. Taher (Saudi Dental Journal)
Objectives: This study aimed to assess the bi-axial flexural strength of two dual-polymerizing resin luting agents cemented to human dentin when photo-activated with different light-curing units. Materials and methods: Two dual-cured resin cements: choice (CH) and Variolink II (VL) were tested. Hybrid composite resin (Z-250) discs (12 × 1.5 mm) were fabricated. Three types of light-curing units were used halogen-curing unit (QTH), light-emitting diode (LED) and plasma arc (PAC). Sixty dentin discs of 0.5 mm thickness were prepared from extracted human teeth. A circular mold (2.5 mm in height and 12 mm diameter) was utilized to create supporting structure for dentin, resin cement complex. The resin luting cement (0.5 mm) was placed on the previously prepared dentin discs and covered with the prefabricated composite discs. Photo-activation of cements was performed for 40 s with QTH and LED units and for 3 s with PAC. The specimens were divided into 12 groups (20 specimens for each light source). Six groups were kept in distilled water for 24 h and the rest were stored for 6 weeks. Bi-axial flexural strength was determined using Instron machine. The data was analyzed using two-way ANOVA and Tukey test for comparison. Results: The findings indicated that the bi-axial flexural strength values for both cements CH and VL were higher for 24 h over 6 weeks but not statistically significant when cured with QTH. Meanwhile, when LED light was used for photo-activation the cements, the flexural strength values reported were statistically higher of 24 h over 6 weeks storage at P = 0.4E−6 However, PAC light did not record any statistically significant difference between two duration for the CH cement although when used for polymerization of VL the reported value for 6 weeks were statistically significantly higher value than 24 h duration at P = 0.002. Conclusion: When high immediate flexural strength is preferred in clinical situation photo-activation the cements with LED reported the greatest value. Keywords: Bi-axial flexural strength, Light-curing unit, Resin cement, Dual curing cement